Communication-based Da'wah Ethics Inspired by the Prophet's Sunnah in the Qur'an - Sabil Mokodenseho; Muh. Idil MS; Sahara Yarbo; Fatmawaty Toani; Liliana Korompot; Fadlun Pakelo; Elvi Dotinggulo (Westscience Press, 2024)
The concept of Da'wah, or the invitation to Islam, is deeply rooted in Islamic teachings, with communication playing a pivotal role in its execution. This research aims to conduct a comprehensive literature review analysis on communication-based Da'wah ethics inspired by the Prophet's Sunnah as depicted in the Qur'an. Through an exploration of relevant literature, this paper will elucidate the principles and practices of ethical communication in Da'wah activities, drawing insights from the Qur'an and the exemplary conduct of the Prophet Muhammad (peace be upon him). By synthesizing existing scholarship, this study seeks to provide a nuanced understanding of communication ethics in Da'wah efforts, highlighting their significance in contemporary contexts.